2021
DOI: 10.1111/bdi.13122
|View full text |Cite
|
Sign up to set email alerts
|

Chronotypes and circadian rest–activity rhythms in bipolar disorders: a meta‐analysis of self‐ and observer rating scales

Abstract: Objective Chronobiological models postulate that abnormalities in circadian rest/activity rhythms (CRAR) are core phenomena of bipolar disorders (BDs). We undertook a meta‐analysis of published studies to determine whether self‐ or observer ratings of CRAR differentiate BD cases from comparators (typically healthy controls [HCs]). Method We undertook systematic searches of four databases to identify studies for inclusion in random effects meta‐analyses and meta‐regression analyses. Effect sizes (ES) for pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Other large-scale community cohort studies demonstrated associations between the amplitude and stability of circadian rhythms in BD [34]. Furthermore, systematic reviews and metaanalyses of cross-sectional studies of individuals with BD compared with healthy controls repeatedly suggest that circadian dysrhythmias are more common in patients, even in euthymia [16,35]. Nevertheless, there is still some debate about the state or trait nature of these abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other large-scale community cohort studies demonstrated associations between the amplitude and stability of circadian rhythms in BD [34]. Furthermore, systematic reviews and metaanalyses of cross-sectional studies of individuals with BD compared with healthy controls repeatedly suggest that circadian dysrhythmias are more common in patients, even in euthymia [16,35]. Nevertheless, there is still some debate about the state or trait nature of these abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Second, chronobiological models offer a plausible explanation of the observed phenomenology of BD [15]. Third, several self-and observer-rated tools can be used to evaluate sleep quality, chronotypes or other aspects of sleep-wake patterns in clinical settings [13,16]. Fourth, studies have shown that these self-or observer-rated sleep disturbances assessed during inter-episode periods are associated with BD relapse or recurrence [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Although the e-Delphi focused on RARs in patients with cancer, the recommendations highlight that disordered RARs can also occur in other clinical conditions. These include patients with neurodegenerative conditions (e.g., Parkinson's disease and Alzheimer's disease), psychiatric disorders (e.g., bipolar disorder), and respiratory disease (e.g., chronic obstructive pulmonary disease) [23][24][25][26]. Currently, evidence is insufficient Several factors highlighted in the recommendations modify circadian RARs to varying extents and should be considered during an assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies analyzing circadian preferences of patients with bipolar disorder confirmed that patients with bipolar disorder prefer the evening type [ 51 - 54 ]. In a longitudinal follow-up study of patients with bipolar disorder, the evening type was associated with sleep disturbance regardless of mood episodes.…”
Section: Circadian Rhythm and Circadian Preference (Type)mentioning
confidence: 99%